Karamunting Leaf Extract (Rhodomyrtus tomentosa (Aiton) Hassk.) as antibiofilm on Escherichia coli - Sabrina, Tia; Mansur, Muhammad Syafi’i; Diba, Masayu Farah; Nawawi, Rizki Andini; Tamzil, Nia Savitri (Bioeksperimen: Jurnal Penelitian Biologi, 2025)
Escherichia coli is a bacterium that causes many serious infections such as digestive tract, urinary tract and bloodstream infections. One of the main challenges in treating this bacterial infection is the formation of biofilm, which increases bacterial resistance to antibiotics. As an alternative to overcome antibiotic resistance, karamunting has been identified as having antibacterial potential against Gram-negative bacteria, including E. coli. The active compounds in these leaves have been shown to inhibit bacterial growth and biofilm formation. This research describes the activity of karamunting leaf extract against the anti-biofilm E. coli. The thick karamunting leaf extract was then made into three variations of concentration, namely 125µg/mL, 250µg/mL and 500µg/mL. The parameter measured for the eradication test is the thickness of the biofilm which is read using the Elisa Reader 590nm. In this study, the eradication percentages for the three concentrations were obtained -92.15% at a concentration of 125 µg/mL, -187.24% at a concentration of 250 µg/mL and 52.78% at a concentration of 500 µg/mL. Karamunting leaf extract has activity as an antibiofilm against E. coli bacteria. Karamunting leaf extract with a concentration of 500 µg/mL is the Minimum Inhibitory Concentration (MIC) which is effective as an antibiofilm on E. coli.